Adapting EFL Teaching to Student’s Learning Styles in some Secondary Schools in Beninese Republic - EGOUNLETI, Pédro Marius (My University, 2022)
This research aims at identifying both teaching and learning styles of Beninese EFL teachers and learners so as to examine the impacts of these styles on students’ academic performance. Quantitative and descriptive research approaches have been used to collect data in 10 state-owned and private secondary schools through (2) types of questionnaire addressed to 20 EFL teachers and 200 students. In addition, a structured focus -group was organised with 12 EFL teachers to better understand their teaching style preferences as well as their impacts on their students’academic achievements The analysis of the data collected reveals that EFL students are different from each other in various ways; there is no standard teaching style and that a variety of technical and methodological resources is needed in the classroom so as to meet all learners’ needs; a match in teaching and learning styles enhances students’ motivation and achievement whereas a mismatch results in students’ failure. In order to prevent any hindrance to EFL teaching and learning process, this study suggests that EFL teachers be aware of their students’ learning styles and try to harmonize them to their teaching practices. It also recommends that government recruit enough professionally qualified EFL teachers and organize seminars and periodical trainings for them.
Keywords: Teaching practices-Learning styles-EFL students-Performance